2018
DOI: 10.1017/epi.2018.51
|View full text |Cite
|
Sign up to set email alerts
|

Representation in Models of Epistemic Democracy

Abstract: Epistemic justifications for democracy have been offered in terms of two different forms of information aggregation and decision-making. The Condorcet Jury Theorem is appealed to as a justification in terms of votes, and the Hong–Page ‘diversity trumps ability’ result is appealed to as a justification in terms of deliberation in the form of collaborative search. Both results, however, are models of full and direct participation across a population. In this paper, we contrast how these results hold up within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The model we describe here is based on the model developed by Daniel Singer that provides a straightforward agent-based representation of the Hong-Page model by imposing a rugged landscape on a 2000 unit ring that agents explore using 3-tuple heuristics [23]. Singer's model has also been used in other analyses of the Hong-Page model [24,47]. However, where both the base Hong-Page Model and Singer's representation of it assume that communication between agents working together is lossless and costless, we introduce the possibility of…”
Section: Extending the Hong-page Model To Include Miscommunicationmentioning
confidence: 99%
“…The model we describe here is based on the model developed by Daniel Singer that provides a straightforward agent-based representation of the Hong-Page model by imposing a rugged landscape on a 2000 unit ring that agents explore using 3-tuple heuristics [23]. Singer's model has also been used in other analyses of the Hong-Page model [24,47]. However, where both the base Hong-Page Model and Singer's representation of it assume that communication between agents working together is lossless and costless, we introduce the possibility of…”
Section: Extending the Hong-page Model To Include Miscommunicationmentioning
confidence: 99%
“…On the other hand, this disadvantage may be outweighed by the fact that representatives usually have much more resources for improving their competence than average citizens. For example, they regularly engage in extensive deliberation and collaborative search before they pass laws (Grim et al 2020), and as party members they benefit from their party's institutional and procedural mechanisms that inform their opinions and enhance their knowledge (Ebeling 2016). For this reason, Goodin and Spiekermann (2018: Ch.…”
Section: The Condorcet Jury Theorem (Cjt)mentioning
confidence: 99%
“…Then, we explored whether two democratic processes (voting and/or debate) would successfully reflect the majority’s opinion in a representative hierarchy similar to that possessed by most advanced modern democratic countries. We modeled various opinion pooling rules, from a direct democracy in which collective decisions are made by majority rule to a representative democracy in which collective decisions are made by elected officials representing a group of people (Grim et al, in press). Simulation results indicated that when collective decisions are made solely by a vote, direct majority voting is epistemologically superior to a representational structure.…”
Section: Primary Research Contributionsmentioning
confidence: 99%
“…Our current model of rational polarization demonstrates how polarization might arise from rational information processing. Building from it, we plan to include other parameters into the model—path dependence, sharedness of arguments (majority or minority), diversity (Grim et al, 2019, in press), comparative contexts (intergroup and intra group), issue types (subjective or objective), hierarchical representation, and interaction communities (communication across social networks). This model and its associated extensions aim to shed light on the continuing political polarization in American politics.…”
Section: Future Directions and Empirical Validationmentioning
confidence: 99%